2019
DOI: 10.3390/jcm8111979
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Stem Cells from Systemic Sclerosis Patients Maintain Pro-Angiogenic and Antifibrotic Paracrine Effects In Vitro

Abstract: Innovative therapies based on autologous adipose-derived stem/stromal cells (ASC) are currently being evaluated for treatment of systemic sclerosis (SSc). Although paracrine angiogenic and antifibrotic effects are considered the predominant mechanisms of ASC therapeutic potential, the impact of SSc on ASC paracrine functions remains controversial. In this study, phenotype, senescence, differentiation potential, and molecular profile were determined in ASC from SSc patients (SSc-ASC) (n = 7) and healthy donors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 45 publications
0
27
1
Order By: Relevance
“…In this regard, contradictory results are available about the properties of ASCs isolated from patients affected by autoimmune and chronic inflammatory diseases. For example, some reports demonstrated that ASCs from patients affected by systemic sclerosis show the same phenotypical and functional characteristics of their healthy counterparts (Scuderi et al, 2013;Capelli et al, 2017;Velier et al, 2019), while Griffin et al (2017) observed that ASCs from sclerodermic patients showed identical phenotype and differentiation capacity of those from healthy donors, but displayed reduced proliferation and migration capacity. Whilst, the presence of cardiovascular risk factors in cardiac patients seems to reduce ASC pluripotency and self-renewal, thus discouraging their autologous use in the clinical setting (Dimmeler and Leri, 2008;Krawiec et al, 2016).…”
Section: The Road Ahead In Immunomodulatory Potential Of Ascsmentioning
confidence: 99%
“…In this regard, contradictory results are available about the properties of ASCs isolated from patients affected by autoimmune and chronic inflammatory diseases. For example, some reports demonstrated that ASCs from patients affected by systemic sclerosis show the same phenotypical and functional characteristics of their healthy counterparts (Scuderi et al, 2013;Capelli et al, 2017;Velier et al, 2019), while Griffin et al (2017) observed that ASCs from sclerodermic patients showed identical phenotype and differentiation capacity of those from healthy donors, but displayed reduced proliferation and migration capacity. Whilst, the presence of cardiovascular risk factors in cardiac patients seems to reduce ASC pluripotency and self-renewal, thus discouraging their autologous use in the clinical setting (Dimmeler and Leri, 2008;Krawiec et al, 2016).…”
Section: The Road Ahead In Immunomodulatory Potential Of Ascsmentioning
confidence: 99%
“…Such therapy was safe, well tolerated, and associated with possible transient, beneficial, clinical and peripheral immune-tolerogenic effects [3]. Velier, M. et al indicated that adipose-derived stem/stromal cells (ASC) from systemic sclerosis (SSs) patients maintain pro-angiogenic and anti-fibrotic paracrine effects in vitro, thereby supporting further development of ASC-based autologous therapies for SSc treatment [4]. Buyl, K. et al pointed out the responses and characteristics of MSCs from adipose tissue, following expansion and inflammatory priming that substantially modulated the expression of 28 molecules implicated in immune regulation [5].…”
mentioning
confidence: 99%
“…Histology and immunohistochemistry analyses showed the absence of a fibrotic response, as indicated by a lower scar index than the sham and no increase of cellularity in the wounds. In general, cell-loaded materials, even though they were loaded with half of the cells that were delivered through the direct injection approach, exhibited low levels of total collagen, high levels of mature collagen and high angiogenesis potential, which further advocate the paracrine antifibrotic effect, regenerative/ remodelling capacity and vascularisation competence of ADSCs [54][55][56]. The injected hADSCs resulted in higher collagen deposition, which could be related to a slower activity during the remodelling phase [57,58].…”
Section: Discussionmentioning
confidence: 99%